Online Registration Application Quality and User Satisfaction: A WebQual 4.0 and EUCS-Based Study at a Private Hospital in Indonesia - Khofidhotur Rofiqoh; Merita Arini (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: The digitalization of hospital services increasingly requires high-quality online registration applications to enhance efficiency and user experience. Ineffective registration processes characterized by long queues, delays, and occasional system bottlenecks remain a major barrier to service efficiency and patient satisfaction in many hospitals. Online registration applications are expected to address these issues, yet limited studies have specifically examined how the quality of such applications influences user satisfaction, particularly in private hospitals in developing regions. This study examines how application quality, measured using the WebQual 4.0 dimensions, influences user satisfaction based on the End-User Computing Satisfaction (EUCS) model. This integration allows a more comprehensive understanding of how system usability, information attributes, and service interaction collectively shape user perceptions in digital health settings. Methods: A quantitative cross-sectional design was employed using validated instruments adapted from the WebQual 4.0 and End-User Computing Satisfaction (EUCS) models. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). To strengthen analytical depth and support theoretical interpretation, qualitative insights obtained from open-ended responses were incorporated to triangulate and enrich the quantitative findings. Results: The Study found that application quality significantly influenced user satisfaction (p < 0.001). All WebQual 4.0 dimensions, Usability, information quality, and service interaction showed positive and substantial contributions to the model. These findings align with core assumptions of the EUCS model, which posits that user satisfaction emerges from perceptions of system usefulness, information relevance, and overall performance quality. Qualitative responses supported the quantitative findings, indicating that users generally perceived the application as easy to use and informative. However, some noted occasional technical issues and suggested improvement to enhance system performance. Conclusion: Usability, information quality, and service interaction play critical roles in shaping user satisfaction with online hospital registration applications. The findings underscore the theoretical relevance of integrating WebQual 4.0 and EUCS, demonstrating that multidimensional system quality is essential for optimizing patient experience in digital hospital services. These results highlight the need for continuous system refinement to improve usability and service responsiveness, ultimately strengthening digital transformation efforts and enhancing patient-centered service delivery in hospital settings.